Electrodeposition of zinc antimony alloy thermoelectric materials - Nor Hairin, Assayidatul Laila; Romainor, M. N.; Othman, Raihan; Mohd Daud, Farah Diana (Institute of Physics Publishing, 2018)
Zinc antimonite, Zn4Sb3 is a promising thermoelectric material because of its high thermoelectric performance and abundance of Zn and Sb in nature. Thus, in this study, samples of Zn-Sb alloy were prepared using electrodeposition method because of its simple experimental set-up, which also carried out in the room temperature. From the XRD results, all samples deposited exhibit Zn-Sb alloy compositions. The best results were S1 and S3 as they had dominant peaks that showed the crystal lattice of Zn4Sb3. From the SEM images, the surface morphology of Zn-Sb alloy deposited samples showed were all-irregular, course and rough structures. While, the atoms arrangement of the deposited samples were all flowery-like. Based on physical properties characterization, the best samples; S1 (0.1M ZnCl2-0.1M SbCl3, 100mA, 120min) and S3 (0.1M ZnCl2-0.1M SbCl3, 50mA, 120min), were selected and investigated their thermoelectric performances; electrical conductivity and Seebeck coefficient, to determine their power factor, PF. Heat capacity of the samples was also examined to relate it with thermal conductivity of Zn-Sb deposited samples. For thermoelectric performance, S1 obtained power factor of 1.37x10-7V/K. Ω.cm at 102°C with the Seebeck coefficient of 181μV/K. While as for S3, the power factor was 1.58x10-7V/K. Ω.cm with Seebeck coefficient of 113μV/K at 101°C. From DSC analysis, it showed that S3 obtained higher Cp than S1. Cp for S3 was 46.8093mJ/°C while S1 was 38.3722mJ/°C.